The Sufi Text as a Qibla of Intellectual Rebellion: Between the Text’s Defiance and the Reader’s Curiosity - djellil, fatimazohra; Cherifi, fatima (El Omda in Linguistics and Discourse Analysis, 2024)
The Sufi text often provoked the recipient's horizon, who was surprised and overwhelmed by how to deal with the Sufi code. About positioning, and this explains to us his warlike movement, which is not approved by a decision.